The Impact of diet on wound healing after dental surgery - the role of micro- and macronutrients in the regeneration of oral tissues - Rybowski, Jakub; Krzyśkowska, Sylwia; Szczupaj, Maciej; Popiel, Michał; Głowacz, Julia; Dziekoński, Kamil (Quality in Sport, 2025)
The process of wound healing after oral surgery is a complex biological phenomenon influenced by multiple factors, including proper nutrition. Nutrients, both micro- and macronutrients, play a crucial role in oral tissue regeneration by supporting collagen synthesis, cell proliferation, and modulation of inflammation. Vitamins, minerals, and an adequate intake of proteins, fats, and carbohydrates can accelerate the healing process and reduce the risk of complications. The aim of this study is to analyze the available literature on the impact of diet on regenerative processes in the oral cavity, with a particular focus on the role of micro- and macronutrients, as well as the microbiota, and to determine optimal dietary recommendations for patients undergoing oral surgical procedures.